Mandela and the Left. Issue 6 (2nd November 2019) - Lodge, Tom
Abstract : Drawn into the Communist Party's social circles through friendships during the 1940s, Mandela became increasingly interested from 1952 onwards in the party's doctrines and in the Marxist canon that informed their premises. His first encounters with Communists were at a time when the party was beginning to develop its strategic justification for aligning itself with African nationalism, a development that would prompt Communists to begin recruiting and extending their influence among the middle-class African elite. This article explores the implications of Mandela's association with South Africa's Communist left. It reviews the evidence that points to his membership of the party at the end of the 1950s. It explores the party's purpose in drawing Mandela into its embrace and considers the ways in which Mandela's political thinking and actions may have been shaped by his proximity to South African Communists between 1952 and 1962. Whether Mandela actually thought of himself at that time as a communist is open to question. Through the 1950s and later, he remained receptive to a range of political ideas and captive to none.